'A bright eye to the main chance' : Brogdens' Navvies - British labourers building New Zealand's railways : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in History, at Massey University, New Zealand - Blondell, Delwyn (Massey University, 2020)
Historians have generally regarded the group known as Brogdens' Navvies as part of a special settlement scheme, induced to migrate to provide essential labour. In 1872 British labourers were recruited to construct New Zealand's railway network. The contracting firm John Brogden and Sons became reluctant immigration agents so they could fulfil their agreement with the New Zealand Government for the massive and costly public works undertaking. Rollo Arnold, when studying English immigrants of the 1870s, argued that the navvies were largely from rural backgrounds thus desirable potential settlers. However, history has largely ignored their contribution to settlement as it was engulfed by the government assisted immigrants. Additionally, as their immigration was privately funded, there has been an information deficit about these men and their backgrounds. The investigation collected data on the lives of just over 1,000 men, and the families that accompanied them. The approach combines conventional historical archival research with genealogical methodology, making use of commercial websites like Ancestry and Findmypast. Quantitative research was supplemented by qualitative case studies to determine if Brogden's navvies showed any enduring distinctive identity. This thesis compares Brogdens' Navvies to typical British navvies. It investigates the progress of members of the Brogdens' Navvies group to determine if the cultural narrative that expected immigrants would easily make economic and social advancements was correct in this case. Both British and New Zealand navvy groups included both labourers and tradesmen. Those recruited were some of the poorest in their communities and there was more diversity in their backgrounds than is seen in official records. Navvy culture had much in common with labouring culture generally and railway camps were not exclusively male. Much of the evidence in primary sources focuses on periods when navvies displayed socially undesirable behaviours, usually coinciding with periodic access to money and alcohol. Key findings were their significant contribution to railways, not only in construction but in maintenance, and that a substantial proportion was absorbed quickly and successfully into New Zealand society. Additionally, this study uncovered a greater range of life-paths than was expected from the existing historiography.
Keywords: 430320 New Zealand history